Effect of Abstraction on Permeability and Hydraulic Gradient in a Simulated Unconfined Aquifer Using Sand Tank Model (Journal of Agriculture & Rural Development, 2008)
An experiment was carried out at the Hydraulic Laboratory of the Department of Irrigation and Water Management (IWM), Bangladesh Agricultural University (BAU), Mymensingh during the period from June to October 2003 to observe the effect of abstraction on permeability and hydraulic gradient in a simulated unconfined aquifer using sand tank model. In this study discharge was measured by volumetric method and coefficient of permeability (K) was calculated using Darcys law. For this experiment sand having particle size from 0.006 to 2.0 mm were used. Water elevation of different piezometers was recorded for five different discharge rates such as 0.040, 0.0396, 0.035, 0.0322 and 0.03118 litre per second for layered stratum (Cu=1.76). The average values of coefficient of permeability and hydraulic gradient were 5.00 mm/s and 0.1575 m/m, respectively. For homogeneous formation (Cu=1.5), the discharges were 0.03675, 0.03603, 0.0355, 0.03539 and 0.03318 litre per second, and the calculated average values of coefficient of permeability and hydraulic gradient were 6.276 mm/s and 0.1148 m/m, respectively. Hydraulic gradient for layered stratum was found higher than that of homogeneous formation. Very good linear relationship was found between water elevations and piezometric distances for both layered and homogeneous formations. The correlation coefficient (r) between water elevations and piezometric distances for higher and lower discharges in layered stratum were found to be 0.964 and 0.993 also for homogeneous formations this values were 0.972 and 0.987, respectively. Key words: Discharge, hydraulic gradient, coefficient of permeability, groundwater flow model.